Benefit-Cost Analysis in Infrastructure Development of Coal Railway Transportation in East Kalimantan Province - Mustamina Maulani; Dinda Annissa Larasati; Yanif Dwi Kuntjoro (Journal of Earth Energy Science, Engineering, and Technology, 2018)
Benefit-Cost Analysis (BCA) is an analysis of the calculation of benefits and cost of development plans that are used to make public decisions that will impact on the welfare of society. East Kalimantan provincial government is building railway infrastructure in cooperation with PT. Railway Borneo (PT KAB) representative for Indonesia from Russian Railways (RZhD) to transport coal. This study analyzed the benefits and costs derived from the construction of the railway was based on economical factors. Is expected to enhance regional energy security. And cost benefit analysis used to evaluate the use of economic resources so that scarce resources can be used efficiently, because the government has many programs or projects to be implemented while the costs are very limited. Benefits to the railway infrastructure development projects for the coal sector in the province of East Kalimantan, among others, have environmentally friendly energy infrastructure in the context of national development in accordance with RPJMN. Increase national income for central and local governments due to the stimulation of high import. Increased foreign or local investors to be able to invest in Indonesia. Coal transportation cost savings, time savings and ease of delivery of coal, and create new jobs that can impact on people's welfare. Costs arising from the construction of the railway to the coal sector by, among others, the cost of investment incurred for the construction consisting of maintenance costs, costs of operations and so forth, open land, government regulations overlap, the surrounding environment. and maintenance costs and provide guidance on the surrounding community.